1992
DOI: 10.1111/j.1365-2958.1992.tb02205.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ribosomal protein S1 from Escherichia coli and Micrococcus luteus on protein synthesis in vitro by E. coli and Bacillus subtilis

Abstract: We have designed a set of nine plasmids containing the Bacillus pumilis cat gene with one of three Shine-Dalgarno (SD) sequences (weak, strong or stronger) and one of three initiation codons (AUG, GUG or UUG). These constructions have been used to determine the effect of ribosomal protein S1, SD and initiation codon sequences and Escherichia coli ribosomal protein S1 on translation in vitro by E. coli and B. subtilis ribosomes. Translation of these nine constructions was determined with three types of ribosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…31) Inactivation of ypfD, which encodes the S1 homologue in B. subtilis, 32) also caused a considerable decrease in sporulation at high temperature (Table 3). Sorokin et al 33) reported previously that ypfD (designated it as the gene jofD) is expressed but is not essential in B. subtilis.…”
Section: Discussionmentioning
confidence: 99%
“…31) Inactivation of ypfD, which encodes the S1 homologue in B. subtilis, 32) also caused a considerable decrease in sporulation at high temperature (Table 3). Sorokin et al 33) reported previously that ypfD (designated it as the gene jofD) is expressed but is not essential in B. subtilis.…”
Section: Discussionmentioning
confidence: 99%
“…4) (8, 32). Therefore, rates of initiation of translation of mRNAs from all three operons will likely be low (8,32), and thus levels of the proteins encoded by these operons will also be low. Consequently, it FIG.…”
Section: Vol 188 2006mentioning
confidence: 99%
“…The problem of overexpression is particularly severe when genes from Gram-positive bacteria are cloned in a Gram-negative host. Gram-positive bacteria use ribosomal binding sequences which are close to the consensus sequence for efficient translation initiation (Farwell et al, 1992 ;Isono & Isono, 1976). This can be avoided, or at least reduced, by using a lowcopy-number vector, in particular when a large-insert library is required to provide a scaffold of the entire bacterial genome.…”
Section: Large-insert Librariesmentioning
confidence: 99%